Establishment of Dynamic Properties for Malaysian Peat Soil Using Multichannel Analysis of Surface Waves - Zainorabidin, Adnan; Basri, Kasbi; Koh , Ann Ang; Mohamad, Habib Musa; Abu Talib, Mohd Khaidir; Md Yusof, Zeety; Pakir, Faizal; Salikin, Amirzaki (International Journal of Integrated Engineering, 2024)
A poor understanding of peat behavior has introduced several engineering problems including differential settlements or slides which greatly impact society. Problematic characteristics of peat including a high moisture content and the presence of fresh fibers, cause a significant challenge in obtaining high-quality samples for laboratory-based investigation. Therefore, the application of in-situ geophysical methods is sought to mitigate these problems. The dynamic properties of a peat deposit in West Malaysia are described in this study. The Multichannel Analysis of Surface Waves (MASW) was conducted at six different locations. These peat soils had considerably different characteristics due to the different natures of decomposed materials. The samples obtained from the five locations had organic contents of 66.5 to 97.1%, water contents of 447 to 964%, and fiber content between 22.1 and 75.2%. Based on Von Post classification, the peat type ranged from H3 (fibrous) to H8 (amorphous). Shear wave velocity (Vs) and maximum shear modulus (Gmax) are presented, and their dependence on variables such as moisture content, organic content, fiber content, specific gravity and bulk density are illustrated. The general trend shows an increase in Vs and Gmax with decreasing moisture, organic and fiber content of peat soil. The difference in the degree of humification did not result in significant differences in Vs and Gmax obtained. The results showed that the value of Vs and Gmax ranged from 24.0 to 67.1m/s and 0.40 to 7.06 MPa respectively. Correlation between the index and dynamic properties peat shows that the Vs and Gmax increase as the moisture, organic and fiber content decreases. Successful determination of in-situ Vs and Gmax on peat soil minimized the potential of underestimation due to sample disturbance and provide a sustainable, rapid and economic method.